Erotisme Dalam Tradisi Tasawuf - Syaifan Nur; Mukhlis Mukhlis (Ulumuna, 2006)
When people talk about erotism, the first thing in the mind of most people are nudity, sexuality, and vulgarity. It exploits mostly women’s sexual organs for sale or—in the proponents’ point of view—for the sake of art and freedom of expression. For this reason the moralists who are worried too much about morality, stand in the first line to fight against all kinds of expression intended to arouse sexual desire publicly. In the field of Islamic thought it has been becoming an endless debate between the Scholars of fiqh and the Islamic mysticism. The Scholars of fiqh accused the Gnostic practicioners of just making up the rules in religion (bid’ah) which contaminate the holiness of God through their erotic works of rhyming. On the other hand, the Sufi claims to look at the case from the essence rather than the physical appearance.